Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2147/vhrm.s287082
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Therapies for Heart Failure: Current Insights and Future Potential

Abstract: Despite the current reductionist approach providing an optimal indication for diagnosis and treatment of patients with heart failure with reduced ejection fraction (HFrEF), there are no standard pharmacological therapies for heart failure with preserved ejection fraction (HFpEF). Although in its infancy in cardiovascular diseases, the epigenetic-based therapy ("epidrugs") is capturing the interest of physician community. In fact, an increasing number of controlled clinical trials is evaluating the putative ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 78 publications
(136 reference statements)
0
15
0
Order By: Relevance
“…In conclusion, including an original ML method in a classic RNA-seq bioinformatic analysis, we showed that some additional features could emerge, and it is possible to draw out a more complete biological picture of the pathophysiology of HF [ 29 ]. Although a limitation of the study may be the low sample size due to the type of biospecimen, as these samples are rare, the study represents a significant contribution in the research area investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, including an original ML method in a classic RNA-seq bioinformatic analysis, we showed that some additional features could emerge, and it is possible to draw out a more complete biological picture of the pathophysiology of HF [ 29 ]. Although a limitation of the study may be the low sample size due to the type of biospecimen, as these samples are rare, the study represents a significant contribution in the research area investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, a growing number of epigenetic compounds were unveiled and tested for the treatment of a wide spectrum of human diseases [43]. Of note, several of these drugs have already been approved by the Food and Drugs Administration (FDA) (Table 1) [44][45][46][47][48][49][50][51]. Inhibitors of histone deacetylases (HDAC) -such as sodium butyratehave shown to blunt myocardial inflammation (i.e.…”
Section: Epidrugs In Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%
“…The repurposed drugs with a possible indirect epigenetic interference, including metformin, statins, sodium glucose transporter inhibitors 2 (SGLT2i), and omega 3 polyunsaturated fatty acids (PUFAs), have been identified by a number of preclinical and clinical experiments as having the cardioprotective effects in cardiac cells (163,192). Specifically, it was reported that metformin could ameliorate cardiac fibrosis (193).…”
Section: The Repurposed Drugsmentioning
confidence: 99%
“…Statins may also participate in the prevention and treatment of CVDs through histone modifications (195). There are still few randomized trials have been carried out to evaluate whether the potential epigenetic-oriented effects of these non-canonical repurposed drugs, which were not originally developed as epidrugs, were involved in their cardioprotective effects against different clinical phenotypes of heart failure (163).…”
Section: The Repurposed Drugsmentioning
confidence: 99%